An Integration Of Taguchi Method And Response Surface Methodology (Rsm) On Injection Moulded Pp Gears For Parameters Optimization - Jamaludin, Amirul Aliff (2015)

(untitled)
Recent years, much attention has been paid to material recycling of plastics, which exhibits many advantages as compared to other kind of processes. Thus, the plastic recycling is widely utilized in the reuse of waste during the industrial processing of plastics. However, the changes in properties during recycling process still remain unclear, for instance, to anticipate the performance of products made of recycled plastics. In this research, usability of reprocessed polypropylene (PP) up to 15 cycles as substitute for virgin PP is investigated by evaluating the influence of processing parameters on shrinkage and mechanical properties. An integrated optimization approach based on Taguchi method and response surface methodology (RSM) analysis was utilized to optimize the quality properties of injection molded gears. Considering the functionality and application of the product, tooth thickness shrinkage, addendum circle shrinkage, dedendum circle shrinkage, ultimate strength, Young‘s modulus and elongation at break are selected as the performance measured of moulded gear. In this research, the experiments have been conducted by using L18 Taguchi‘s experimental orthogonal arrays design to identify only on the significant factors. As a result of Taguchi‘s screening experiment, melt temperature, mould temperature, injection pressure, injection time and packing time was identified as significant processing parameters that have a great influence on PP gear shrinkage and mechanical properties of PP gear. Considering the interaction effect between the significant processing parameters, a mathematical model has been established in xv order to investigate the influence of processing parameters on produced gear‘s quality properties. Finally, the desirability function analysis is performed with an intention to simultaneously enhance both of shrinkage and mechanical properties of produced gears under one set of optimal processing parameters setting. Results of the optimal multi-response optimization show that the melt temperature was set to 220.03 ºC, mould temperature was set to 40 ºC, injection pressure was set to 99.98 bar, injection time was set to 3s and packing time was set to 14.83 s in order to get both of optimal PP gear‘s shrinkage and mechanical properties. The results drawn through this study can be of great significance to the practitioners, in optimization of shrinkage and mechanical properties of injection moulded PP gears with a minimum number of experiments trials and processing cost.